2017
DOI: 10.1097/wnr.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological dynamic brain connectivity during symbolic magnitude comparison in children with different mathematics achievement levels

Abstract: Children with mathematical difficulties usually have an impaired ability to process symbolic representations. Functional MRI methods have suggested that early frontoparietal connectivity can predict mathematic achievements; however, the study of brain connectivity during numerical processing remains unexplored. With the aim of evaluating this in children with different math proficiencies, we selected a sample of 40 children divided into two groups [high achievement (HA) and low achievement (LA)] according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…either encouraged or discouraged right-or left-handers participate or it was not clear from description of the methods whether participants were right-handed on purpose or by chance were excluded (e.g., Gómez-Velázquez et al, 2017;González-Garrido et al, 2018;Grabner et al, 2009;Stanescu-Cosson et al, 2000;Strang & Rourke, 1983).…”
Section: No Selection Of Participants On the Basis Of Their Handednesmentioning
confidence: 99%
“…either encouraged or discouraged right-or left-handers participate or it was not clear from description of the methods whether participants were right-handed on purpose or by chance were excluded (e.g., Gómez-Velázquez et al, 2017;González-Garrido et al, 2018;Grabner et al, 2009;Stanescu-Cosson et al, 2000;Strang & Rourke, 1983).…”
Section: No Selection Of Participants On the Basis Of Their Handednesmentioning
confidence: 99%
“…Handedness: Studies that either encouraged or discouraged right-or lefthanders participate or it was not clear from description of the methods whether participants were right-handed on purpose or by chance were excluded (e.g., Gómez-Velázquez et al, 2017;González-Garrido et al, 2018;Grabner et al, 2009;Stanescu-Cosson et al, 2000;Strang & Rourke, 1983). Those studies were excluded following a conservative approach.…”
Section: Study Selectionmentioning
confidence: 99%
“…There have also been efforts at the Instituto de Neurociencias to characterize MLD and electrophysiological level. Recently, the Laboratory of Clinical Neurophysiology reported ERP components (Gómez-Velázquez, Berumen, & González-Garrido, 2015), EEG coherence (González-Garrido et al, 2018) and brain connectivity (Gómez-Velázquez et al, 2017) of 40 elementary school children with different maths performance levels comparing symbolic and non-symbolic numerical quantities. Their results showed that children with low performance show lower P2P and P3 amplitudes, but more extended coherence topographic patterns that involve mainly frontoparietal areas, and higher connectivity in these areas.…”
Section: Mathematical Learning Difficultiesmentioning
confidence: 99%
“…En el Instituto de Neurociencias también se han hecho esfuerzos para caracterizar las DAM y el nivel electrofisiológico. Recientemente, el Laboratorio de Neurofisiología Clínica reportó los componentes de los PREs (Gómez-Velázquez, Berumen, & González-Garrido, 2015), la coherencia del EEG (González-Garrido et al, 2018), y la conectividad cerebral (Gómez-Velázquez et al, 2017) de 40 niños de la escuela primaria con diferentes niveles de rendimiento en matemáticas, mientras comparaban cantidades numéricas simbólicas y no simbólicas. Sus resultados mostraron que los niños con bajo rendimiento revelan amplitudes P2P y P3 inferiores, pero patrones topográficos de coherencia más extensos que incluyen principalmente las áreas frontoparietales, y una mayor conectividad en esas áreas.…”
Section: Dificultades En El Aprendizaje De Las Matemáticasunclassified